2016
DOI: 10.1002/lary.26323
|View full text |Cite
|
Sign up to set email alerts
|

Risk of tinnitus in patients with sleep apnea: A nationwide, population‐based, case‐control study

Abstract: 3b. Laryngoscope, 127:2171-2175, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 34 publications
(52 reference statements)
2
25
0
Order By: Relevance
“…One of our previous studies found that sleep apnea was associated with an increase in the incidence of primary central nervous system cancers [17]. Another study from our group revealed that the risk of tinnitus was significantly higher among middle-aged and elderly Taiwanese patients with sleep disturbances, especially with sleep apnea [24]. Possible mechanisms linking tinnitus and brain tumor might involve the effect of poor sleep on enhanced proinflammatory cytokine production, which leads to immunosuppression [25].…”
Section: Discussionmentioning
confidence: 99%
“…One of our previous studies found that sleep apnea was associated with an increase in the incidence of primary central nervous system cancers [17]. Another study from our group revealed that the risk of tinnitus was significantly higher among middle-aged and elderly Taiwanese patients with sleep disturbances, especially with sleep apnea [24]. Possible mechanisms linking tinnitus and brain tumor might involve the effect of poor sleep on enhanced proinflammatory cytokine production, which leads to immunosuppression [25].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Doctors, however, are still in the dark ages of carrying around printed handbook guides or flash cards, which are often obsolete, or rely on access to computer terminals for intranet-based guidelines. Ofcom figures report that 71% of UK adults own a smartphone, 4 and a recent survey shows more than 98% of doctors own a smartphone. 5 It is demonstrated that there are many positive uses for doctors incorporating modern smartphone technology to deliver health care.…”
Section: Correspondence: Our Experiencementioning
confidence: 99%
“…3 The relationship of tinnitus with sleep-disordered breathing (SDB) and obstructive sleep apnoea (OSAS) has rarely been mentioned. 4 In a recent population-based case-control study, the risk of tinnitus was found to increase 1.36 times in patients with OSAS. However, no detailed grading or severity of SDB (or OSAS) and tinnitus was provided.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sleep apnea is associated with higher risks of several significant adverse effects on various body systems, such as a 2 to 4 times higher risk of arrhythmia, a 3 times higher risk of stroke, and greater mortality from both heart failure and stroke . Sleep apnea is characterized by snoring‐related vibration, hypoventilation, and hypoxia; it may damage the carotid artery, brain, and inner ear . Previous studies have found that patients with sleep apnea exhibit increasing risks of dizziness, tinnitus, and hearing loss .…”
Section: Introductionmentioning
confidence: 99%